Exposure of Red Knots (Calidris canutus rufa) to Select Avian Pathogens; Patagonia, Argentina - D'amico, Veronica Laura (2007)
As part of the shorebird surveillance, Red Knots (Calidris canutus rufa) were sampled in two Patagonian sites in Argentina, Rý´o Grande and San Antonio Oeste, during 2005–2006. Cloacal swabs and serum samples were collected from 156 birds and tested by virus isolation (Newcastle disease virus), polymerase chain reaction (PCR; avian influenza virus and Plasmodium/Hemoproteus), and for antibodies to St. Louis encephalitis virus. All test results were negative.Calidris canutus rufa) were sampled in two Patagonian sites in Argentina, Rý´o Grande and San Antonio Oeste, during 2005–2006. Cloacal swabs and serum samples were collected from 156 birds and tested by virus isolation (Newcastle disease virus), polymerase chain reaction (PCR; avian influenza virus and Plasmodium/Hemoproteus), and for antibodies to St. Louis encephalitis virus. All test results were negative.